2017
DOI: 10.20960/nh.1070
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre calidad de vida, actividad física, alimentación, y control glucémico con la sarcopenia de adultos mayores con diabetes mellitus tipo 2.

Abstract: IntroducciónLa sarcopenia se define como la pérdida de masa muscular y su deterioro funcional asociado a la edad, por lo que tiene un alto impacto sobre la calidad de vida. Sin embargo, la prevalencia de la sarcopenia en diabetes mellitus tipo 2 (DM2) no está suficientemente estudiada.ObjetivosAnalizar la prevalencia de sarcopenia en mayores de 65 años con DM2 y la posible influencia de la actividad física, la alimentación, el control glucémico, el sexo, la edad y calidad de vida.MétodosParticiparon 279 pacien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
1
7
0
15
Order By: Relevance
“…Baker et al 40 observed that high adiponectin concentrations are associated with weight loss, low density, and skeletal muscle mass, in addition to functional limitation in older adults aged 70-79 years, which may be a factor for the development of sarcopenia in individuals of this age group. 41 Casals et al 42 observed that the reduction of muscle mass in older adults can negatively affect glucose regulation, impacting muscle tissue. When comparing the results of this study with those of Esteves et al 9 (WC: ≤ 86 cm for women and ≤ 97 cm for men) and Confortini et al 11 (WC: 88 cm for women and 92 cm for men), the results were higher in sensitivity for both sexes and in specificity for men, reinforcing the utility of WC as a viable indicator for sarcopenia in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al 40 observed that high adiponectin concentrations are associated with weight loss, low density, and skeletal muscle mass, in addition to functional limitation in older adults aged 70-79 years, which may be a factor for the development of sarcopenia in individuals of this age group. 41 Casals et al 42 observed that the reduction of muscle mass in older adults can negatively affect glucose regulation, impacting muscle tissue. When comparing the results of this study with those of Esteves et al 9 (WC: ≤ 86 cm for women and ≤ 97 cm for men) and Confortini et al 11 (WC: 88 cm for women and 92 cm for men), the results were higher in sensitivity for both sexes and in specificity for men, reinforcing the utility of WC as a viable indicator for sarcopenia in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Es reconocida la influencia de la acidosis metabólica de la IRC sobre la resistencia a la insulina, la inflamación crónica y la disfunción mitocondrial. Además, pudiera no existir el efecto benéfico de la insulina endógena al evitar la pérdida de masa muscular (31,32). estos aspectos ameritan una investigación con diseño analítico.…”
Section: Discussionunclassified
“…Si bien son mediciones fáciles y se siguieron técnicas rigurosas y estandarizadas, estos resultados pueden estar sesga-Sin embargo, como fortaleza, es el primer estudio en estos centros hospitalarios que midió la presencia de sarcopenia. Estos resultados resaltan la necesidad de tomar más en cuenta este aspecto que muchas veces pasa desapercibido para los médicos pero que puede afectar la calidad de vida de los pacientes 40 .…”
Section: Parámetrosunclassified